Yeha, Äthiopien. Archäologische Untersuchungen auf dem Kirchenvorplatz von Yeha. Die Arbeiten der Jahre 2013 bis 2018 - Japp, Sarah (e-Forschungsberichte des DAI, 2019)
Between 2013 and 2018 a stratigraphic sondage was conducted in Yeha under the umbrella of the Ethiopian-German project. Aim of the excavation was to get a chronological sequence of the settlement. The lowest stratum of the trench, situated directly above the natural rock, revealed a settlement predecessor of the late 2nd millennium BC followed by Ethio-Sabaean occupation layers from the first half of the 1st millennium BC. After a gap in the second half of the 1st millennium BC settlement started again in the early Aksumite period. From the late Aksumite period onwards a continuous usage of the site can be assumed until modern times.